Automated Sorting Conveyor Using Pneumatic Actuators for Industrial Applications at Morowali Metal Industry Polytechnic - Setiawan, Angga Tegar; Suwandy, Suwandy; Wijayanto, Hendi Lilih; Arohman, Abdul Wahid (Jurnal Teknologi dan Manajemen, 2024)
The use of automatic sorting systems in industry plays a crucial role in saving time and reducing manual labor through automation. The main challenges are the high error rate and slow manual sorting processes. This research aims to design and develop an automatic sorting conveyor system using Arduino technology and pneumatic actuators to enhance sorting efficiency and accuracy. The proposed solution is a system capable of detecting and sorting objects based on size with very low error rates, thereby increasing productivity and reducing human error. The design and development of this system involve creating a 3D model of components such as the conveyor frame, belt, motor, pneumatic actuators, and sensors, and integrating them into a complete system. Testing was conducted with seven differently sized test objects to evaluate the system’s performance in detecting and sorting objects based on size and height. Input and output voltage measurements ensure performance in line with the expected specifications. The research results demonstrate that the developed automatic sorting conveyor system effectively sorts objects with high accuracy. The system can detect and sort objects based on size with a 0% error rate, reducing the time required for the sorting process compared to manual methods. The use of pneumatic actuators and appropriate sensors ensures consistent and reliable system performance. The test results indicate that the system can be integrated into various industrial applications to enhance production efficiency. The developed automatic sorting conveyor system successfully improves the efficiency and accuracy of the sorting process in industry. It shows significant potential for reducing human error and increasing productivity, making it a practical solution for various industrial applications.